Humanity and Justice: An Analytical Study of the Philosophical Interpretation from the Perspective of Syed Muhammad Naquib Al-Attas - Kaulan, Rezki; Nuha, Dzatu Aliviatin; Fardyatullail, Haila; Delahara, Nindhya Ayomi (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2025)
One of the most pressing and multifaceted challenges in contemporary society is the issue of justice in human life. Social inequality, discrimination, and disparities in access to fundamental rights - such as education, economic opportunities, and healthcare - serve as tangible evidence that justice often remains an abstract ideal without equitable implementation. This study examines the concept of humanity and justice in Islam through the interpretive framework of Syed Muhammad Naquib al-Attas, with a focus on: (1) the definition of justice, (2) the individual as the subject of justice, (3) individual freedom as the foundational principle of justice, and (4) equality as a critical prerequisite for justice. Employing a qualitative research design, this study utilizes a descriptive-analytical method combined with a philosophical exegesis approach, interpreting Qur'anic verses through philosophical theory. The findings indicate that humans, as moral agents, play a pivotal role in the realization of justice. Justice, as a core Islamic principle, originates from divine revelation and embodies balance, harmony, and the proper allocation of all things to their rightful place. Justice is achieved when individuals, acting as its practitioners, consciously and freely acknowledge and submit to Allah as the Creator, fulfill their obligations, and equitably honor the dignity of others. Al-Attas underscores the human role as vicegerents (khali>fah) on earth, bearing the responsibility to uphold justice in alignment with human nature (fitrah). Furthermore, ethics and one’s relationship with God are identified as essential foundations for fostering justice within society and the state.